2014
DOI: 10.1186/cc13741
|View full text |Cite
|
Sign up to set email alerts
|

Residents learning ultrasound-guided catheterization are not sufficiently skilled to use landmarks

Abstract: IntroductionUltrasound-guided (UG) technique is the recommended procedure for central venous catheterization (CVC). However, as ultrasound may not be available in emergency situations, guidelines also propose that physicians remain skilled in landmark (LM) placement. We conducted this prospective observational study to determine the learning curve of the LM technique in residents only learning the UG technique.MethodsDuring the first three months of their rotation in our ICU, residents inexperienced in CVC use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 13 publications
0
13
1
1
Order By: Relevance
“…In contrast to previous studies, we found no evidence that the adoption of ultrasound guidance by trainees is associated with reduced proficiency in landmark-based methods(18). This may be because the two methods share a common requisite skill set, and becoming proficient in the landmark-based approach flows naturally from first learning ultrasound-based techniques.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies, we found no evidence that the adoption of ultrasound guidance by trainees is associated with reduced proficiency in landmark-based methods(18). This may be because the two methods share a common requisite skill set, and becoming proficient in the landmark-based approach flows naturally from first learning ultrasound-based techniques.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, we looked for evidence supporting the hypothesis that the adoption of ultrasound by trainees comes at the expense of proficiency in landmark based methods(18). Evaluating only palpation-guided procedures, we found no significant differences in outcomes between trainees who exclusively utilized the palpation method (n= 23 trainees, n = 65 procedures, 16.7 ± 9.6 minutes) compared to trainees who were capable of utilizing either ultrasound or palpation (n = 22 trainees, n = 61 procedures, 16.4 ± 7.8 minutes, p = 0.915) (Supplemental Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, 1 study demonstrated that after an educational intervention, residents inserting CVCs had increased their success rate to approximately 90% after 10 ultrasound-guided catheter insertions (compared with approximately 80% after 1 to 3 insertions), and the rate of complications was (and persisted at) approximately 8% after only 4 catheter insertions (compared with approximately 13% after 1 to 3 insertions). 25 Another study of CVC insertion suggested that up to 50 procedures were needed to reduce complications from subclavian line insertions, 3 while a study of colonoscopy showed that up to 80 procedures were necessary for improved patient care. 7 Bariatric surgery yearly volumes of over 150 were also associated with better performance and lower complications compared with lower-volume practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Assessors should be expert providers who regularly perform the ultrasound-guided procedure in a similar practice environment. 9,[89][90][91][92][93][94] For example, providers who are not hospitalists but who are experts in an ultrasound-guided procedure and commonly perform it on the hospital wards would be acceptable assessors. However, a radiologist who only performs that procedure in a fully-staffed interventional radiology suite with fluoroscopy or computed tomography guidance would not be an acceptable assessor.…”
Section: Assessors Should Be Unbiased Expert Providers Who Have Demonmentioning
confidence: 99%